Comparative Study on Water Resources Carrying Capacity of Key River Basins in the Pearl River Region - JIN Zhanwei; SUN Bo; LIU Hechang (Renmin Zhujiang)
In this paper,the evaluation index system of water resources carrying capacity was built in terms of three dimensions of water resources carrying subject,carrying object,and approach.TOPSIS model,coupling coordination model,and production function model were used to analyze the water resources carrying status of 27 key basins in the Pearl River region.The results show that the water resources carrying capacity of Nandu River,Guijiang River,Wanquan River,and Beijiang River basins rank first,and that of Jiuzhou River,Huangni River,Qinjiang River,and Jianjiang River Basins rank second.The internal elements of the water resources system in the key basins are mainly characterized by near imbalance,with 17 near imbalance basins,nine mild imbalance basins,and one moderate imbalance basins.The water resource carrying efficiency curve of key basins shows three types:low,medium,and high.There are four low-efficiency basins,12 medium-efficiency Basins,and 11 high-efficiency basins.A comprehensive comparison of water resources carrying capacity ranking,coupling coordination degree,and carrying efficiency shows that the water resource carrying capacity of the Jiuzhou River,Jianjiang River,and Qinjiang River Basins is poor,while that of the Beijiang River,Xijiang River,Wushui River,Hejiang River,and Tingjiang River Basins is relatively good.The results in this paper can be an important reference for the planning,development,utilization,protection,and management of water resources in the Pearl River region and key river basins.